2010
DOI: 10.1016/j.jhsa.2010.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strength of the Side-to-Side Versus Pulvertaft Weave Tendon Repair

Abstract: Purpose-The side-to-side (SS) tendon suture technique was designed to function as a repair that permits immediate post-operative activation and mobilization of a transferred muscle. This study was designed to test the strength and stiffness of the SS technique against a variation of the Pulvertaft (PT) repair technique.Methods-Flexor digitorum superficialis (FDS) and flexor digitorum profundus (FDP) tendons were harvested from four fresh cadavers and used as a model system. Seven SS and six PT repairs were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 22 publications
3
115
6
1
Order By: Relevance
“…There was no difference, however, in cross-sectional area between both techniques. 2 The double-loop technique also had a significant difference when compared with the PW regarding ultimate strength. Regrettably, it too is at a disadvantage in that the repair looks like a knot making it bulky, and thus creating greater friction with surrounding tissues.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There was no difference, however, in cross-sectional area between both techniques. 2 The double-loop technique also had a significant difference when compared with the PW regarding ultimate strength. Regrettably, it too is at a disadvantage in that the repair looks like a knot making it bulky, and thus creating greater friction with surrounding tissues.…”
Section: Discussionmentioning
confidence: 98%
“…A commonly described failure is instability of the sutures leading to elongation of the junction. 2 Also, the weave is bulky, which creates a greater amount of friction on the surrounding tissue. 8 It is thought that reducing this bulkiness improves the ability of the repaired tendons to glide through the surrounding tissue, resulting in less friction and thus fewer adhesions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to insure stability and permit immediate mobilization, which is critical when performing transfers through IOM, the overlap between the donor and recipient tendon was 5 cm (Fig. 2, inset) (Brown et al, 2010). For the traditional group (palmar transfer), all procedures were the same with the exception that BR was passed palmar to the radius and secured to FPL.…”
Section: Methodsmentioning
confidence: 99%
“…A biomechanical study revealed that both the Pulvertaft 3-and 4-weave repair could allow early and safe active mobilization [85]. The main problem with the Pulvertaft weaving is failure by the suture knots either slipping or pulling through the tendon, and a step-cut side-to-side tendon suture is an alternative to reduce bulkiness that is mostly observed with the use of the Pulvertaft weaving [86,87].…”
Section: Case Presentationmentioning
confidence: 99%